2018
DOI: 10.1080/09553002.2018.1511926
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression-based biodosimetry for radiological incidents: assessment of dose and time after radiation exposure

Abstract: Purpose: In order to ensure efficient use of medical resources following a radiological incident, there is an urgent need for high-throughput time-efficient biodosimetry tools. In the present study, we tested the applicability of a gene expression signature for the prediction of exposure dose as well as the time elapsed since irradiation. Materials and methods: We used whole blood samples from seven healthy volunteers as reference samples (X-ray doses: 0, 25, 50, 100, 500, 1000, and 2000 mGy; time points: 8, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 53 publications
2
29
0
Order By: Relevance
“…that are better suited to estimate low doses only (< 0.1 Gy) 11 . At the gene transcription level, all the biomarkers tested here have been shown to be radiation responsive markers in multiple tissue types 11,13,45,46 while several of them (BAX, FDXR, DDB2 and p53) have been used in the development of a gene expressionbased signature for the reconstruction of dose in human peripheral blood 45,[47][48][49][50] . We consider that future studies should further investigate the gene to protein relationship of these blood biomarkers for radiation biodosimetry.…”
Section: Discussionmentioning
confidence: 99%
“…that are better suited to estimate low doses only (< 0.1 Gy) 11 . At the gene transcription level, all the biomarkers tested here have been shown to be radiation responsive markers in multiple tissue types 11,13,45,46 while several of them (BAX, FDXR, DDB2 and p53) have been used in the development of a gene expressionbased signature for the reconstruction of dose in human peripheral blood 45,[47][48][49][50] . We consider that future studies should further investigate the gene to protein relationship of these blood biomarkers for radiation biodosimetry.…”
Section: Discussionmentioning
confidence: 99%
“…The early transcriptional response to radiation is a process that is almost entirely regulated by the activation status and level of P53, which in its turn depends on residual DNA-damage. This renders this response inherently transient and most of the P53-dependent changes in gene expression have therefore returned to the baseline levels within 24 to 48 h after exposure [37,38]. At the same time, these early changes in gene expression after irradiation, mostly from blood cells, have been shown to be very practical for the purpose of retrospective biodosimetry, in which radiation doses are predicted based on the gene expression profiles [3,39].…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, these early changes in gene expression after irradiation, mostly from blood cells, have been shown to be very practical for the purpose of retrospective biodosimetry, in which radiation doses are predicted based on the gene expression profiles [3,39]. However, one of the main drawbacks of gene expression for biodosimetry is the transient nature of the effect [37]. We observed long-term induction of circular transcripts of Pvt1 in the blood of whole-body irradiated mice, while the mRNA was unchanged.…”
Section: Discussionmentioning
confidence: 99%
“…Since the early 2000's, many studies have demonstrated the usefulness of radiation-induced changes in gene expression as signatures that could be used for biodosimetry purposes [reviewed in Hall et al (2017), Lacombe et al (2018), and Pernot et al (2012)]. With time and the development of new methods for gene expression profiling, these studies have shown an increasing sensitivity of gene signatures towards prediction of ever lower doses, down to 100 mGy and below (Broustas et al 2017;Knops et al 2012;Macaeva et al 2018;Macaeva et al 2016;Nosel et al 2013;Paul and Amundson 2011;Riecke et al 2012), the dose range to which astronauts may be exposed. An important new application in this respect will be the identification of exon signatures, based on the observations of extensive radiation-induced alternative splicing (Macaeva et al 2016;Sprung et al 2011) which will benefit from advances in RNA sequencing methods.…”
Section: Transcriptomic Profilingmentioning
confidence: 99%